A-Z for Spanish AB initio : essential vocabulary organized by topic for IB Diploma - Zago, Noelia (England : Elemi International Schools Publisher, 2021)
Part of the A-Z series from Elemi which aims to support students throughout their IB Diploma studies, this A-Z for Spanish Ab Initio provides a glossary of Spanish-English vocabulary: Essential vocabulary and key phrases organized in topics to reflect the five conceptual themes of IB Diploma Spanish Ab Initio. Entirely focused on the needs of the IB Diploma curriculum, students learn and engage with current topical vocabulary across a variety of text types. Provides a useful reference to help students express their own ideas and opinions in written and spoken Spanish. Offers a range of appropriate vocabulary and key phrases to develop students' interactive skills and help them maintain a conversation. This popular book specifically offers help with: learning and engaging with appropriate and varied vocabulary in topic-by-topic lists developing writing skills in a variety of text types supporting speaking skills, particularly as part of the internal assessment.
Keywords: Spanish Language; Spanish language -- Textbooks for foreign speakers -- English